Diffusion Tensor Imaging in Radiation-Induced Myelopathy - Keřkovský, Miloš; Zitterbartová, Jana; Pour, Luděk; Šprláková-Puková, Andrea; Mechl, Marek (Journal of neuroimaging, 2014)
Radiation myelopathy (RM) is a rare complication of spinal cord irradiation. Diagnosis is based on the history of radiotherapy, laboratory tests, and magnetic resonance imaging of the spinal cord. The MRI findings may nevertheless be quite unspecific. In this paper, we describe the findings of diffusion tensor imaging in a case of the delayed form of RM. We observed areas of restricted diffusion within the spinal cord which probably corresponded to the ischemic changes. This would concur with the currently accepted pathogenetic theory concerning RM.
Keywords: diferenciální diagnóza; zobrazování difuzních tenzorů; výsledek terapie; Radiation Injuries; lidé; Treatment Outcome; Diagnosis, Differential; Radiotherapy, Conformal; nádory páteře; Male; radiační poranění; Spinal Neoplasms; konformní radioterapie; Diffusion Tensor Imaging; Spinal Cord Diseases; lidé středního věku; nemoci míchy; mužské pohlaví; Middle Aged; Humans